Implementing Health in All Policies - Time and Ideas Matter Too!; Comment on "Understanding the Role of Public Administration in Implementing Action on the Social Determinants of Health and Health Inequities" - Carole Clavier (Kerman University of Medical Sciences, 2016)
Carey and Friel suggest that we turn to knowledge developed in the field of public administration, especially new public governance, to better understand the process of implementing health in all policies (HiAP). In this commentary, I claim that theories from the policy studies bring a broader view of the policy process, complementary to that of new public governance. Drawing on the policy studies, I argue that time and ideas matter to HiAP implementation, alongside with interests and institutions. Implementing HiAP is a complex process considering that it requires the involvement and coordination of several policy sectors, each with their own interests, institutions and ideas about the policy. Understanding who are the actors involved from the various policy sectors concerned, what context they evolve in, but also how they own and frame the policy problem (ideas), and how this has changed over time, is crucial for those involved in HiAP implementation so that they can relate to and work together with actors from other policy sectors.